STRATEGI MENINGKATKAN KINERJA UMKM DI SERENAN, JUWIRING, KABUPATEN KLATEN - Burhanudin Ahmad Yani; Ratna Damayanti; Istiatin Istiatin (STIE Pelita Nusantara Semarang, 2019)
Micro, Small and Medium Enterprises (MSMEs) are business activities that contribute to improving economic conditions, especially the rural economy. However, the development of Micro, Small and Medium Enterprises (MSMEs) is very slow in competition with large companies in the era of free trade and globalization. Therefore all problems must be found the best solution with various efforts so that MSMEs perform well. The purpose of this study was to analyze and determine the improvement in the performance of MSMEs in Serenan, Juwiring District, Klaten Regency by observing both the influence of internal and external factors partially or jointly. The research methodology used is quantitative descriptive type. through the Survey directly to the research location, the population of this study was wood processing MSMEs (furniture) which were in Serenan, Juwiring, Klaten Regency totaling 34 producers. The sample in this study is a population of 34 producers. While the sampling technique used was the census of all producers in the Serenan Sub-District which numbered 34 questionnaire answers. The results showed that the performance of MSMEs in Serenan, Juwiring, Klaten Regency was significantly influenced by internal factors (consisting of aspects of HR, financial aspects, production aspects and marketing aspects) and external factors (aspects of government policy, aspects of socio-economic aspects and related institutions) both partially and together.